Elevated heart rate and nondipping heart rate as potential targets for melatonin: a review. Issue 2 (1st July 2016) - Simko, Fedor; Baka, Tomas; Paulis, Ludovit; Reiter, Russel J.
Abstract: Elevated heart rate is a risk factor for cardiovascular and all‐cause mortalities in the general population and various cardiovascular pathologies. Insufficient heart rate decline during the night, that is, nondipping heart rate, also increases cardiovascular risk. Abnormal heart rate reflects an autonomic nervous system imbalance in terms of relative dominance of sympathetic tone. There are only a few prospective studies concerning the effect of heart rate reduction in coronary heart disease and heart failure. In hypertensive patients, retrospective analyses show no additional benefit of slowing down the heart rate by beta‐blockade to blood pressure reduction. Melatonin, a secretory product of the pineal gland, has several attributes, which predict melatonin to be a promising candidate in the struggle against elevated heart rate and its consequences in the hypertensive population. First, melatonin production depends on the sympathetic stimulation of the pineal gland. On the other hand, melatonin inhibits the sympathetic system in several ways representing potentially the counter‐regulatory mechanism to normalize excessive sympathetic drive. Second, administration of melatonin reduces heart rate in animals and humans. Third, the chronobiological action of melatonin may normalize the insufficient nocturnal decline of heart rate. Moreover, melatonin reduces the development of endothelial dysfunction and atherosclerosis, which are considered a crucial pathophysiological disorder of increased heart rate and pulsatile blood flow. The antihypertensive and antiremodeling action of melatonin along with its beneficial effects on lipid profile and insulin resistance may be of additional benefit. A clinical trial investigating melatonin actions in hypertensive patients with increased heart rate is warranted.